2020
DOI: 10.1080/25787489.2020.1844520
|View full text |Cite
|
Sign up to set email alerts
|

Week 96 subgroup analyses of the phase 3, randomized AMBER and EMERALD trials evaluating the efficacy and safety of the once daily darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) single-tablet regimen in antiretroviral treatment (ART)-naïve and -experienced, virologically-suppressed adults living with HIV-1

Abstract: & on behalf of the AMBER and EMERALD study groups (2021): Week 96 subgroup analyses of the phase 3, randomized AMBER and EMERALD trials evaluating the efficacy and safety of the once daily

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…A previous study demonstrated that transforming TDF into TAF significantly improved the eGFR of patients (34), which further supports the renal safety of TAF. Although previous studies have indicated that the conversion from TDF to TAF can increase blood lipid and TC levels due to the increasing LDL-C, the ratio of TC/high-density lipoprotein remain unaltered (21,35). The present study demonstrated that TAF treatment did not affect blood lipid levels or the degree of hepatic steatosis within 48 weeks.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A previous study demonstrated that transforming TDF into TAF significantly improved the eGFR of patients (34), which further supports the renal safety of TAF. Although previous studies have indicated that the conversion from TDF to TAF can increase blood lipid and TC levels due to the increasing LDL-C, the ratio of TC/high-density lipoprotein remain unaltered (21,35). The present study demonstrated that TAF treatment did not affect blood lipid levels or the degree of hepatic steatosis within 48 weeks.…”
Section: Discussioncontrasting
confidence: 67%
“…Among them, 45 patients were hepatitis B e antigen (HBeAg)-positive. A total of 61 patients (age, 42.13±12.30) were followed up for 24 weeks, of whom 42 were followed up for 48 weeks (age, 43.39±13.41), including35 patients who were tested HBeAg-positive. According to the baseline ALT levels, 61 patients were divided into group A [ALT≤50 U/l; upper limit of normal (ULN).85-1.51 mmol/l, respectively.…”
mentioning
confidence: 99%
“…This study had limited follow-up of participants receiving cobicistat-boosted protease inhibitors; therefore, it is unclear if the impact is the same with cobicistat. In a subgroup analysis at week 96 of the AMBER and EMERALD trials, eGFR cystatin was stable in the darunavir/cobicistat/TAF/FTC arm, and there were no case of subclinical proximal renal tubulopathy [29]. Boosted darunavir remains an important option for treatment experienced PLWH and these data provide support for minimal renal effects, especially when used with TAF.…”
Section: Protease Inhibitorsmentioning
confidence: 79%
“…8,19,37 Despite these differences in weight gain between genders, a prior study of virologically-suppressed patients previously treated with a boosted PI and switching to DRV/c/FTC/TAF found that other outcomes (such as the proportion of patients experiencing virologic rebound or patient adherence to medication) were similar between males and females. 38 Similar to the assessment of weight and BMI change, the identification of predictors of weight or BMI increase ≥5% in both cohorts was also limited by a small sample size, resulting in the inclusion of a limited number of predicting factors in the models.…”
Section: Weighted N=325mentioning
confidence: 99%